THE USE OF BLENDED LEARNING IN TEACHING WRITING RECOUNT TEXT TO THE TENTH GRADE STUDENTS OF SMA NEGERI 20 MEDAN - Nurul Aulia; Anni Holila Pulungan; Yeni Erlita (Universitas Negeri Medan, 2021)
THE USE OF BLENDED LEARNING IN TEACHING WRITING RECOUNT TEXT TO THE TENTH GRADE STUDENTS OF SMA NEGERI 20 MEDAN *Nurul Aulia **Anni Holila Pulungan **Yeni Erlita ABSTRACT This research dealt with blended learning used by the teachers in teaching writing recount text. The objectives of this study were (1) to explain the use of blended learning for teaching writing recount text to the tenth grade students; (2) to analyze the problems faced by teachers of using blended learning in teaching learning process of writing recount text. This study was qualitatively conducted that involved two English teachers of SMA Negeri 20 Medan. The data were collected by using recording, interview and observing the whole processes of teaching writing. The findings of this study showed that both teachers used the three processes in blended learning setting, such as: conventional learning, emphasizes learning actively and interactive learning. It was also found that the use of blended learning was used in the scientific approach activity. There were four problems faced by teachers in using blended learning, such as the problem of the traditional mindset, the problem of managing and assessing learner progress, bandwidth, and confusion in using the application. Both teachers faced different problems in their classes. Keywords: Blended learning, teaching, writing